Who gets treated for influenza: A surveillance study from the US Food and Drug Administration's Sentinel System. (5th September 2022) - Cocoros, Noelle M.; Haug, Nicole; Cosgrove, Austin; Panozzo, Catherine A.; Sorbello, Alfred; Francis, Henry; Garcia, Crystal; Orr, Robert; Toh, Sengwee; Dutcher, Sarah K.; Measer, Gregory T.
Abstract: Objective: We describe the baseline characteristics and complications of individuals with influenza in the US FDA's Sentinel System by antiviral treatment timing. Design: Retrospective cohort design. Patients: Individuals aged ≥6 months with outpatient diagnoses of influenza in June 2014–July 2017, 3 influenza seasons. Methods: We identified the comorbidities, vaccination history, influenza testing, and outpatient antiviral dispensings of individuals with influenza using administrative claims data from 13 data partners including the Centers for Medicare and Medicaid Services, integrated delivery systems, and commercial health plans. We assessed complications within 30 days: hospitalization, oxygen use, mechanical ventilation, critical care, ECMO, and death. Results: There were 1, 090, 333 influenza diagnoses in 2014–2015; 1, 005, 240 in 2016–2017; and 578, 548 in 2017–2018. Between 49% and 55% of patients were dispensed outpatient treatment within 5 days. In all periods >80% of treated individuals received treatment on the day of diagnosis. Those treated on days 1–5 after diagnosis had higher prevalences of diabetes, chronic obstructive pulmonary disease, asthma, and obesity compared to those treated on the day of diagnosis or not treated at all. They also had higher rates of hospitalization, oxygen use, and critical care. In 2014–2015, among those aged ≥65 years, the rates of hospitalization were 45 per 1, 000 diagnoses among those treated on day 0; 74 per 1, 000 among those treated on days 1–5; and 50 per 1, 000 among those who were untreated. Conclusions: In a large, national analysis, approximately half of people diagnosed with influenza in the outpatient setting were treated with antiviral medications. Delays in outpatient dispensed treatment were associated with higher prevalence of comorbidities and higher rates of complication.